Utilization of Styrofoam Waste as an Additive in AC-BC Mixture with Variations in Compaction Temperature - Theovani, Gabriel Julio; Azwansyah, Heri; Mayuni, Siti (Jurnal Teknik Sipil, 2025)
Styrofoam, a polystyrene-based plastic widely used in packaging, poses serious environmental challenges due to its non-biodegradable nature. Its use as an additive in asphalt mixtures provides dual benefits: reducing plastic waste and improving pavement performance. This study evaluates the effects of styrofoam addition and variations in compaction temperature on the Marshall characteristics of Asphalt Concrete"“Binder Course (AC"“BC). The research included testing the physical properties of aggregates and asphalt, determining the optimum asphalt content (OAC) using the Barchart method in accordance with Bina Marga Specifications 2018, Revision II, and preparing mixtures with styrofoam contents of 0%, 3%, 6%, and 9%. Samples were compacted at 110 °C, 125 °C, and 140 °C, then tested using the Marshall method to analyze stability, flow, and void-related parameters. Results showed an OAC of 5,6%. Higher styrofoam content and compaction temperature generally improved mixture stability. The highest stability value, 1.152,2 kg, was achieved at a 9% styrofoam content and a compaction temperature of 140 °C. These findings indicate that styrofoam enhances structural strength by filling voids without significantly reducing flexibility. Therefore, styrofoam has strong potential as an eco-friendly additive to improve asphalt performance while helping reduce plastic waste.